2012
DOI: 10.4103/0975-7406.99044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroalcoholic extract of Hypericum perforatum on selected traditional and novel biochemical factors of cardiovascular diseases and atherosclerotic lesions in hypercholesterolemic rabbits: A comparison between the extract and lovastatin

Abstract: Context:Evidence suggests that diets with high contents of cholesterol will increase serum lipoproteins and apolipoproteins, thereby increase risk of atherosclerosis. According to literature, some plants show hypolipidemic, hypocholestrolemic, and antiatherosclerotic activities.Aims:In this study, antiatherosclerotic effect of Hypericum perforatum hydroalcoholic extract on hypercholesterolemic rabbits was compared with that of lovastatin.Materials and Methods:Twenty five mature male New Zealand rabbits were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Our results revealed no significant changes in HDL-CH levels in the rats treated with EHP. In contrast with Zou et al, Asgary et al reported that EHP was able to increase HDL-CH levels ( 1 , 3 ). In addition, it has been previously shown that the flavonoid components of H. perforatum can increase HDL-CH levels by augmenting the synthesis of apolipoprotein A-I ( 12 ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our results revealed no significant changes in HDL-CH levels in the rats treated with EHP. In contrast with Zou et al, Asgary et al reported that EHP was able to increase HDL-CH levels ( 1 , 3 ). In addition, it has been previously shown that the flavonoid components of H. perforatum can increase HDL-CH levels by augmenting the synthesis of apolipoprotein A-I ( 12 ).…”
Section: Discussionmentioning
confidence: 70%
“…A growing body of evidence suggests that patients with high levels of total cholesterol (TCH), high levels of low-density lipoprotein cholesterol (LDL-CH), and low levels of high-density lipoprotein cholesterol (HDL-CH) are at a greater risk of atherosclerosis and coronary artery disease ( 1 - 3 ). Oxidative stress plays an important role in the etiology of these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanized-PXR mice are resistant to high-fat diet-induced obesity, similar to that found in PXR knockout mice [44], findings that are consistent with a protective function for human PXR and that question the value of interpreting the previous knockout mouse studies as relevant to humans. In further support of a protective role for PXR, pharmacological activation using St John's Wort extract (containing the potent PXR activator hyperforin) improved lipid profiles and reduced atherosclerosis in the high-fat fed rabbit [45].…”
Section: Xenobiotic Receptorsmentioning
confidence: 95%
“…Hypericum perforatum extracts contain several compounds with biological activity such as hypericin, pseudohypericin, flavonoids, oligomeric procyanidins and hyperforin [3]. In traditional medicine, this extract is used in patients with depression disorders [4]; it possesses antiviral and antibacterial activities and was reported to be beneficial in the management of hyperlipidemia and atherosclerosis [3]. Hypericum perforatum is well tolerated and does not cause major side effects, and it is considered a safe herbal therapeutic agent [5,6].…”
Section: Introductionmentioning
confidence: 99%